De novo fatty-acid synthesis and related pathways as molecular targets for cancer therapy - Mashima, T (Nature Publishing Group, 2009)
Enhanced lipid biosynthesis is a characteristic feature of cancer. Deregulated lipogenesis plays an important role in tumour cell survival. These observations suggest that enzymes in the lipid synthesis pathway would be rational therapeutic targets for cancer. To this end, we review the enzymes in de novo fatty-acid synthesis and related pathways.